Efficacy of repetitive transcranial magnetic stimulation in cognitive impairment of neurodegenerative diseases: a systematic review and meta-analysis - Zhang, Yu; Xu, Ke; Wang, Yulin; Shen, Yiwei; Liu, Zhengnan; Zhang, Chengguang; Zhou, Yan; Lv, Peizhu; Bai, Yan; Wang, Shun (BMC neurology, 2025)
Currently, there is a lack of reliable evidence to prove the effectiveness of repetitive transcranial magnetic stimulation (rTMS) in the cognitive and emotional domains of neurodegenerative diseases (ND), leading to the absence of a unified and effective rTMS treatment protocol or stimulation targets. This systematic review and meta-analysis summarizes existing evidence to evaluate the efficacy of rTMS targeting the dorsolateral prefrontal cortex (DLPFC) and non-DLPFC in the cognitive and emotional aspects of ND. For two common types of ND Alzheimer's disease (AD) and Parkinson's disease (PD), we included 17 relevant randomized controlled trials (RCTs) from five databases. Search terms included rTMS, Parkinson's disease, Alzheimer's disease, cognitive impairment, and randomized controlled studies. Two independent reviewers assessed the risk of bias in the included literature, performed data extraction, and evaluated the evidence. Treatment effects were assessed using the Montreal Cognitive Assessment (MoCA), the Mini-Mental State Examination (MMSE), the Hamilton Depression Rating Scale (HAMD), the Hamilton Anxiety Rating Scale (HAMA), and Activities of Daily Living (ADL). Data were analyzed using R software to evaluate effect sizes and 95% confidence interval (CI). Heterogeneity tests were conducted to assess differences in treatment effects between DLPFC and non-DLPFC. We screened 3,467 articles and identified 17 studies that met the inclusion criteria. The pooled results showed significant effects: MoCA (MD: 2.13, 95% CI [0.75, 3.52], p < 0.001); MMSE (MD: 1.16, 95% CI [0.91, 1.41], p = 0.0075); HAMD (MD: -2.63, 95% CI [-6.45, -1.20], p = 0.14); HAMA (SMD: -0.62, 95% CI [-0.91, -0.33], p < 0.001); ADL (MD: -0.56, 95% CI [-1.10, 2.22], p = 0.48). rTMS has a positive effect on cognitive impairment and emotional abnormalities associated with ND. There is a significant difference in MoCA scores between rTMS applied to DLPFC and non-DLPFC. DLPFC may serve as a reliable stimulation target for treating non-motor symptoms related to ND (such as cognitive and emotional issues), which is beneficial for developing an rTMS treatment protocol with broad applicability for ND. However, due to the small number of included studies and the indirect nature of the comparison methods, we should interpret these results with caution.